(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article explores the cognitive and lexical-semantic properties of adjectives describing human character in English and Uzbek. It focuses on the similarities and differences in how adjectives are structured and perceived in these languages, emphasizing their cultural and linguistic nuances. The study employs a comparative approach to understand how adjectives reflecting human characteristics manifest across these two languages. It analyzes the impact of cultural, cognitive, and linguistic influences on the formation and use of character-related adjectives.